2004
DOI: 10.1021/jp0458194
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multiple Reaction Pathways for the H + cyc-C3H6 Reaction

Abstract: Reaction pathways for the hydrogen atom plus cyclopropane (cyc-C3H6) reaction are studied using an extrapolated coupled-cluster/complete basis set (CBS) method based on the cc-pVDZ, cc-pVTZ, and cc-pVQZ basis sets. For this activated reaction, results reveal two reaction mechanisms, a direct H-abstraction and a H-addition/ring-opening. The hydrogen-abstraction reaction yields the H2 and cyclopropyl (cyc-C3H5) radical products. The vibrationally adiabatic ground-state (VAG) barrier height is predicted to be 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 35 publications
8
73
0
Order By: Relevance
“…The dissociation energy of 87.6 kcal/mol was found at MRCIþQ/CBS//CAS(10,10)/cc-pVDZ level (were CBS refers to an extrapolation from the aug-cc-pVDZ and aug-cc-VTZ basis sets), [52] which is close to our MRPT(6,4)/ CCD//CAS(6,4)/CCD value. Xia et al [22] report dissociation limits for CH 3 OH !…”
Section: Ohsupporting
confidence: 83%
“…The dissociation energy of 87.6 kcal/mol was found at MRCIþQ/CBS//CAS(10,10)/cc-pVDZ level (were CBS refers to an extrapolation from the aug-cc-pVDZ and aug-cc-VTZ basis sets), [52] which is close to our MRPT(6,4)/ CCD//CAS(6,4)/CCD value. Xia et al [22] report dissociation limits for CH 3 OH !…”
Section: Ohsupporting
confidence: 83%
“…It was first tested on HOOH where its efficiency was established [157]. Yu has contracted the bend but not the stretch basis to compute energy levels for several molecules [159,160,194]. Lee and Light contracted both bend and stretch bases [161,162].…”
Section: Chmentioning
confidence: 99%
“…One caution in developing predictive ability for the bimolecular reactions is, however, that there is the implicit assumption that the reaction proceeds via an initial addition to form the corresponding radical intermediate. Though this assumption is expected to be quite good for the systems studied here, for reactions such as O( 1 D) + methane it has been shown that the reaction proceeds through both direct and the longlived intermediate pathways; 34 then studies of the unimolecular dissociation of the intermediate would only probe the latter pathway for the bimolecular reaction.…”
mentioning
confidence: 97%